Prototype Penyiraman Otomatis Berbasis IOT untuk Multi Zona Tanaman Hias - Hafiyyan Putra Pratama; Dewi Indriati Hadi Putri; Sudjani (Jurnal Sistem Cerdas, 2022)
The greenhouse concept for the cultivation of ornamental plants can optimize the conditioning of a good planting environment because it can protect plants from direct rain, can distribute temperature, divide sunlight evenly and regulate the intensity of watering plants regularly. The important thing to pay attention to in the cultivation of ornamental plants is the intensity of watering plants. Regular watering of plants can be optimized with the help of Internet of Things (IoT) technology so that the process of watering plants becomes a smart watering system. In this study, automatic watering of ornamental plants was divided into 3 zones based on the characteristics of humidity, watering time, and required water quantity. The smart watering system for 3 zones is implemented in the form of a prototype including a monitoring system based on the MQTT protocol